Ameloblastic fibro-odontosarcoma: a case report - Mainenti, P. [UNESP]; Oliveira, G. S.; Valerio, J. B.; Daroda, L. S. L.; Daroda, R. F.; Brandao, G.; Rosa, L. E. B. [UNESP] (Churchill Livingstone, 2009)
This paper reports one case, of an ameloblastic fibro-odontosarcoma (AFOS) affecting the mandible, in a 12-year-old girl. This neoplasm is a rare odontogenic neoplasm. To the authors' knowledge this is the fifteenth case of AFOS reported in English. The patient's chief complaint was a swelling in the face For 6 months. An incisional biopsy was performed diagnosing the case as all ameloblastic fibroma. After radiography ameloblastic fibro-odontoma was diagnosed. Computed tomography was performed and a stereolithography model made to plan the surgical procedures. A hemimandibulectomy followed by a vascularized fibular flap was then proposed. The surgery was uneventful. Microscopic features diagnosed an AFOS. After 23 months of close follow-up there is no sign of recurrence or metastasis. Dental implants were recently placed in the fibular flap.
Keywords: ameloblastic fibro-odontosarcoma; hemimandibulectomy; reconstruction; fibula; stereolithography